IDENTIFIKASI KANDUNGAN FE PADA PASIR BESI HASIL PROSES KONSENTRASI MENGGUNAKAN SLUICE BOX - Putra, Infantri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research was conducted to determine the effect of the slope angle on the sluice tool to obtain % recovery. The sample tested was iron sand obtained from Sukabumi, West Java. From the results of the XRF test, it was found that the iron sand sample contained the most dominant element Fe as much as 65.725%, Si as much as 13%, and Ti as much as 6.76% and the results of the XRD analysis showed that the predominance of the compound present in the sample was F2O3. In addition, the sample is also known to contain Titanium Oxide (TiO2). Also the results of the AAS test on the sample concentrate obtained the Fe content contained 18.01% at the slope of 100 concentrate and 19.15% at the concentration of slope 150 and 200. And the most optimal results are at the smallest slope of 10 degrees and get % recovery of 89%. . In addition to the slope angle, it is also known that the smaller the water discharge, the more optimal the % recovery can be.